Online ordering system of PCK engineering - Lee, Chee Wei (2012)
Online Ordering System of PCK Engineering is an web-based system that helps PCK Engineering to manage their business digitally,and allow customer to make order online.As one of the largest and fastest growing company,online enterprise system becoming a need compared to manual method.Therefore, this system has been developed to helps PCK Engineering to manage their sales and services online.It is a better approach to optimize the relationship between PCK Engineering and customers.There are two target users in this system,admin staff and the customers of PCK Engineering.The system consists of ten modules:login and registration, customize stock specification,make appointment and order, manage order and profile, search product,manage stock and specification,approve order and appointment,advisory administration for admin side function,LiveChat and sales report.Rapid Application Development(RAD)model has been used in this project.The four phases are requirements planning, user design,construction and cutover.The implementation of interface and coding to each module in the system has been completed.The testing shows that the acceptance criteria of the system has achieve the objectives of this project.